A nasalização fonética de vogais átonas em Alagoas: uma análise sociolinguística - Mendonça, Ana Maria Santos de (2019)
According to Câmara Júnior (2009 [1970]), the nasal vowels result from the contact between a vowel and a nasal consonant, for example, in /ˈpoNte/ [ˈpõtɪ] "ponte" e /ˈkama/ [ˈkãmə] “cama". Based on this observation, we can consider two types of nasalization: One phonological nasalization and the other phonetic nasalization. The first has distinctive function and is generated by a categorical application rule. The second, object of this study, is not distinctive and is generated by a rule of variable application. The rule of phonetic nasalization, when applied, results in a nasalized vowel as in [bãˈnãnə] "banana". When the rule is not applied, the vowel remains oral as in [baˈnãnə] "banana". Explaining how this phenomenon works in the Alagoana variety will contribute to the linguistic description of the Portuguese spoken in Alagoas, as well as to the comprehension of nasalization in Brazilian Portuguese in general. In order to identify and analyze the linguistic and social factors related to the application of the rule of phonetic nasalization of unstressed vowels in Alagoas, we work with 7.713 contexts favorable to nasalization. We used the data from the Project Alagoano Portuguese – PORTAL Project, made up of eight municipalities of Alagoas. We analyzed the data using the multilevel logistic regression model, which allowed us to control the variables "individual" and "lexical item" at a more aggregated level. We explain the results based on variationist sociolinguistics, and with the support of trace geometry, lexical phonology and metrical phonology. We conclude that the percentage of application of the nasalization process in Alagoas, 58.4%, is lower than we expected for the Northeast region and that the nasalization process is related to the following linguistic factors: i) vowels [o] and [a] – the posterior middle vowel and the low vowel combine the [-alto] and the [+ back] traits, which makes the position of the tongue, during the articulation of the vowel, close to a horizontal symmetry with the soft palate; ii) tonic vowel in the primitive – nasal vowel must be accentuated, it will remain nasal even when the accent is displaced, this is because the process does not cross morphemes; iii) previous context – the preceding context, when filled by a nasal consonant, favors nasalization, because, in addition to the regressive assimilation, the target vowel also gradually assimilates the nasal trait; iv) posterior context - the posterior context, when filled by the nasal consonant [n], presents an association with nasality, because it is articulated closer to the palate than to the nasal bilabial [m]; and v) morphological border - morphological junctions inhibit the phonetic nasalization rule, which characterizes this type of nasalization as an intralexical process, and it is possible to state that the phonetic nasalization of atonic vowels is a rule that applies at the lexical level; vi) contiguous oral vowels; and vii) postonic vowels. We could not find any explanation for the relation between factors vi) and vii) and the application of the nasalization process. The only social variable correlated with the phonetic nasalization of unstressed vowels was age. The younger the speaker, the more he nasalizes, which characterizes the application of the nasalization process as innovative and evidences the existence of a change in progress favoring nasalization. As for the aggregated variables, we conclude that there is significant interference of lexical items in nasalization, evidenced by the fact that 40.9% of the variation is explained by the variation in lexical items. This variability could be justified by phonological processes not controlled in this research and by the fact that the same word is associated with factors of different linguistic variables.